Improving Mathematical Communication Skills Through The Implementation Of Reasoning And Problem Solving Model - Suryawan, I Putu Pasek (Universitas Pendidikan Ganesha, 2018)
The aim of this classroom action research was to improve the mathematical communication skills of 11th grade IIS students in SMAN 1 Blahbatuh. The subject of this study was 32 11th grade IIS students in SMAN 1 Blahbatuh in academic year 2017/2018. The results showed that the implementation of reasoning and problem solving learning model improved the mathematical communication skills of 11th grade IIS students in SMAN 1 Blahbatuh. The improvement could be seen from the students learning completeness that increased 6,3% from 3,1% in the first cycle became 9,4% in the second cycle and increased to be 78,2% in the third cycle. Besides that, students gave positive responses toward the implementation of reasoning and problem solving learning model with mean score 57,2. The improvement of students’ mathematical communication skills happened because of reasoning and problem solving learning model gave emphasis to students through guided-questions in constructing mathematical ideas, gave more opportunities to students in delivering opinion, and gave guidance and motivation to students.